The Dangers of Hoaxes in Building Civil Society in the Era of the Industrial Revolution 4.0 - Muhamad Basitur Rijal Gus Rijal; Ahyani Hisam; Abdul Basit (International Journal of Social Science and Religion (IJSSR), 2021)
Civil society (civil society) as the ideal structure of society's life that is aspired to, but building a civil society is not easy. There are preconditions that must be met by the community in making it happen. Coupled with technological advances in the era of the Industrial Revolution 4.o like today, where information can spread easily through various online media unlimitedly in spreading hoaxes. This research seeks to uncover the dangers of hoaxes in building civil society. This research uses descriptive analytical method by examining the sources of literature related to building civil society in the Industrial Revolution 4.o. This research found that the public space is a means of free speech; democratic behavior; tolerant; pluralism; and social justice can shape civil society. whereas the impact of hoax news greatly affects the way people perceive a certain issue, so that people cannot distinguish which news is real or fake news which causes them to be incited by fake news that is spread.